2008
DOI: 10.1007/bf03326026
|View full text |Cite
|
Sign up to set email alerts
|

Optimum reaction time, performance and exhaust emissions of biodiesel produced by microwave irradiation

Abstract: While transesterification is well established, there remain considerable inefficiencies in existing transesterification processes. In this study an alternative energy stimulant, ''microwave irradiation'' was used for the production of the alternative energy source, biodiesel. The optimum parametric conditions obtained from the conventional technique were applied using microwave irradiation in order to compare both systems. The results showed that application of radio frequency microwave energy offers a fast, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 128 publications
(73 citation statements)
references
References 30 publications
4
67
0
2
Order By: Relevance
“…This increase is proportional to the decrease in the heating value of biodiesel. Refaat et al (2008b) found that the difference in performance between microwave-enhanced biodiesel and petroleum diesel was not statistically significant; a slight increase in SFC was detected with biodiesel, no significant differences were observed in brake thermal efficiency and the combustion efficiency remained constant using either microwave-enhanced biodiesel or Diesel fuel. Najafi et al (2007) noticed that by adding 20 % of waste vegetable oil methyl ester to petrodiesel fuel the maximum power and torque increased by 2.7 % and 2.9 %, respectively (Najafi et al, 2007).…”
Section: Performance Tests Of Wvo-based Biodieselmentioning
confidence: 88%
See 4 more Smart Citations
“…This increase is proportional to the decrease in the heating value of biodiesel. Refaat et al (2008b) found that the difference in performance between microwave-enhanced biodiesel and petroleum diesel was not statistically significant; a slight increase in SFC was detected with biodiesel, no significant differences were observed in brake thermal efficiency and the combustion efficiency remained constant using either microwave-enhanced biodiesel or Diesel fuel. Najafi et al (2007) noticed that by adding 20 % of waste vegetable oil methyl ester to petrodiesel fuel the maximum power and torque increased by 2.7 % and 2.9 %, respectively (Najafi et al, 2007).…”
Section: Performance Tests Of Wvo-based Biodieselmentioning
confidence: 88%
“…Most of the studies on the base-catalyzed transesterification of WVO reported that maximum conversion to the ester occurred with a molar ratio of 6:1 (Tomasevic and Siler-Marinkovic, 2003;Saifuddin and Chua, 2004;Encinar et al, 2005;Gupta et al, 2007;Meng et al, 2008;Refaat et al, 2008b). Transesterification of pretreated waste rapeseed oil carried out by Yuan et al (2008) showed a maximum conversion at 6.5:1 of methanol to oil ratio, whereas an earlier study by Leung and Guo (2006) found a maximum conversion at a ratio of 7:1.…”
Section: Molar Ratio Of Alcohol To Triglyceridementioning
confidence: 97%
See 3 more Smart Citations